The Influence Of Celebrity Endorsers, Content Marketing, And Product Quality On Purchasing Decisions For Skintific Products (Study On Skintific Product Users In Semarang City) - Faradita, Tiana; Putra, ⁠Febrianur Ibnu Fitroh Sukono (International Publisher, 2024)
This study intends to analyze how Celebrity Endorsers, Content Marketing, and Product Quality influence the purchase decision of Skintific products. This type of research uses quantitative questionnaire data. The respondents of this study were private campus students in Semarang City who had purchased Skintific products. Purposive sampling was used for the sampling process in this study, which amounted to 100 respondents. The sample in this study was done with the formula Malhotra (2006). The number of indicators multiplied by 5 or variables multiplied by 5, there are 100 respondents who can be used to adjust the sample size in this study. The research analysis procedure uses Multiple Linear Regression Analysis, Validity Test, Reliability Test, and Hypothesis Test. This study found that Celebrity Endorser does not have a significant effect on customer decisions to buy Skintific products, Content Marketing has a significant and beneficial influence on customer decisions to buy Skintific products while Product Quality has a positive effect on Skintific product purchase decisions. Companies can leverage this research as a primary source of information to improve profitable business operations and increase market share.